PENGARUH PROFITABILITAS, REPUTASI KAP, AUDIT TENURE DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR BARANG KONSUMEN NON PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018 – 2022 - Melania Nur Safitri; Triana Aggraini (Jurnal Ilmiah Akuntansi, 2024)
This study was conducted to examine the effect of Profitability, KAP Reputation, Audit tenure and Company Size on Audit delay. The sample selection technique in this study used purposive sampling method and obtained 78 companies in the non-primary consumer goods sector listed on the Indonesia Stock Exchange for the period 2018-2022. Based on the purposive sampling method, the amount of data in this study was 390 data. The data analysis used in this research is multiple linear regression analysis using the IBM Statistical Package for the Social Sciences (SPSS) version 22 program. Based on the results of the study, it can be concluded that profitability has an effect on audit delay, while KAP reputation, audit tenure, and company size have no effect on audit delay